L'historiographie tardo-antique et la transmission des savoirs - Blaudeau, Philippe; Nuffelen, Peter (Millennium-Studien / Millennium Studies, 2015)
This volume focuses on the role played by historiography in the selection, processing and transmission of knowledge in Late Antiquity. In particular, the transmission of documents (civil and ecclesiastical, authentic and apocryphal) is studied, the impact of differences in genre, as well as how historical, anthropological, ethnographic, astronomical, and medical notions are reshaped in new cultural traditions.